2011
DOI: 10.1002/nbm.1733
|View full text |Cite
|
Sign up to set email alerts
|

Development of a fast method for quantitative measurement of hyperpolarized 129Xe dynamics in mouse brain

Abstract: A fast method has been established for the precise measurement and quantification of the dynamics of hyperpolarized (HP) xenon-129 ((129)Xe) in the mouse brain. The key technique is based on repeatedly applying radio frequency (RF) pulses and measuring the decrease of HP (129)Xe magnetization after the brain Xe concentration has reached a steady state due to continuous HP (129)Xe ventilation. The signal decrease of the (129)Xe nuclear magnetic resonance (NMR) signal was well described by a simple theoretical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Furthermore, it has been demonstrated that human microglia are activated in the absence of significant neuronal loss in the presence of a low concentration of MeHg (i.e., <300 ppb)19, indicating potential neuroprotective roles of microglia. In fact, recent reports have shown microglia-mediated neuroprotective actions including neurotrophic support during brain development23, neuroprotection against NMDA-induced neurotoxicity24 and global brain ischemia25. Here we report that microglia can detect MeHg low , but their neuroprotective action against MeHg low requires astrocytes.…”
mentioning
confidence: 54%
“…Furthermore, it has been demonstrated that human microglia are activated in the absence of significant neuronal loss in the presence of a low concentration of MeHg (i.e., <300 ppb)19, indicating potential neuroprotective roles of microglia. In fact, recent reports have shown microglia-mediated neuroprotective actions including neurotrophic support during brain development23, neuroprotection against NMDA-induced neurotoxicity24 and global brain ischemia25. Here we report that microglia can detect MeHg low , but their neuroprotective action against MeHg low requires astrocytes.…”
mentioning
confidence: 54%
“…While chemical engineering continued introducing novel Xe host and sensing concepts, particularly for an expanding palette of molecular targets [42] and for improved CEST detection, hardware and pulse sequence development delivered significant progress for Xe MRI in human applications. The combination of (a) modern polarizers including high-performance laser diodes for a wider user community [43], (b) optimized RF antenna systems [44, 45], and (c) adapted readout protocols enabled novel studies of dissolved Xe in different tissues [4648]. Imaging of the human brain has been demonstrated in the meantime [4951] as well as Xe MRI of kidney perfusion [52].…”
Section: General Considerations For Hyperpolarized 129xe Nmrmentioning
confidence: 99%
“…Hyperpolarized 129 Xe MRI has great potential for the study of brain function due to: (i) the absence of a background MR signal for xenon in the biological tissues; (ii) the high sensitivity of the 129 Xe chemical shift to different chemical environments in various tissues; and (iii) the high lipid solubility of xenon in biological tissue and Ostwald solubility in red blood cells and plasma (0.2 and 0.1, respectively) . As a result of these benefits, hyperpolarized 129 Xe has been successfully used for brain MRI by research groups . Recently, Zhou and co‐workers successfully detected the stroke area in a rat brain using hyperpolarized 129 Xe ; Mazzanti and co‐workers applied hyperpolarized xenon for brain functional imaging (fMRI) and demonstrated the feasibility of detecting brain function changes using hyperpolarized 129 Xe .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the amount of hyperpolarized xenon available is limited by the allowed volume of injectable solution and the solution‐tissue partition coefficient. The second method, which is non‐invasive and widely used, involves inhaling hyperpolarized 129 Xe gas through the lung . The inhaled hyperpolarized xenon first enters the lung while in the gas phase, and then diffuses across the alveolar walls and enters the pulmonary capillaries.…”
Section: Introductionmentioning
confidence: 99%